Exposure of cardiac microvascular endothelial cells to harmful stimuli : a study of the cellular responses and mechanisms - Genis, Amanda (Stellenbosch : Stellenbosch University, 2014)
Thesis (PhD)-- Stellenbosch University, 2014.